Effect of Nitrogen Fertilizer and Plant Spacing on Vegetative Growth of Sugar Beet (Beta vulgaris) - Baha Eldin. M. Idris; Wael. A. Marajan; Abubaker Haroun Mohamed Adam (Journal of Agronomy Research, 2021)
Despite the existing several Sugar manufacturing companies in Sudan, there is an acute shortage in sugar supply, therefore the government imports Sugar to bridge the gap. One of the strategies to be followed is the introduction of Sugar beet (Beta vulgaris) crop, mainly for sugar production. This crop has several advantages over Sugarcane such as short duration, less water requirement, in addition to other uses like animal feed. Therefore it became necessary to have good understanding of agricultural operations, cultural practices and adaptation. However, the main objective of this study was to assess the effect of Nitrogen fertilizer and plant spacing on vegetative growth of Sugar beet. This study was conducted at the farm of the College of Agriculture, University of Bahri, Alkadro, Khartoum State-Sudan; during the season 2016/2017. The experiment was arranged in Split plot in Randomized Complete Block Design with six treatments and four replications. Two plant spacing (15 and 20 cm.) were used as main plot, referred as (S1, S2) along with three levels of Nitrogen fertilizer (40, 80 and 120 kg/ha.), as subplot; referred as (N1, N2 and N3) and the control (0). Data regarding leaf number, leaf area index (LAI), leaf dry weight (g) (LDW), root diameter (mm.) and root fresh weight were recorded and statistically analyzed. The results showed S2 (20 cm) increased all the studied plant characters, namely the leaf number (29.139), leaf area index by (7.54), leaf dry weight (g) to (89.870), root diameter (mm) (94,992), root fresh weight (g) (695.80) compared to S1(1015 cm). On the other hand; the application of N3 (120 kg/ha.) increased the lead number (30.956), leaf Area Index (8.841), Leaf dry weight (102.47), root diameter (97.955) and root fresh weight (851.77) compared to S2 and S1 as presented in (table 4, table 5 and table 6).
Keywords: Nitrogen Fertilizer